The word of the cross : reading Paul - Linebaugh, Jonathan A. (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2022)
"A collection of exegetical, historical, and theological essays on Paul's letters, including reception history and comparative readings in conversation with other texts"--
"This collection of Jonathan Linebaugh's most important work on Paul explores the merciful surprise at the heart of Paul's gospel: a grace that, while strange and weak in worldly terms, is nothing less than the power of God, full of comfort and promise. Through twelve essays-two of them new-Linebaugh contextualizes and interprets key Pauline passages, does comparative readings of Paul in conversation with early Jewish texts, and enters into dialogue with Reformation theologians such as Martin Luther and Thomas Cranmer. Thorough and multifaceted, Linebaugh's work is at once exegetical, historical, and theological in scope. Accordingly, The Word of the Cross is a rigorous scholarly enterprise that takes seriously Paul's claim that the good news of Jesus Christ, despite appearing scandalous and foolish, in fact contradicts and overcomes the conditions of the possible through the power of God"--
Machine generated contents note: Table of ContentsForeword by John M. G. Barclay -- Preface: A Merciful Surprise -- Part One: Reading Paul -- 1. Righteousness Revealed: The Death of Christ as the Definition of the Righteousness of God in Romans 3:21-26 -- 2. Promises beyond the Possible: Grace and the God Who . . . in Romans 4 -- 3. Not the End: The History and Hope of God's Unfailing Word in Romans 9-11 -- 4. The Speech of the Dead: Identifying the No Longer yet Now Living I of Galatians 2:20 -- Part Two: Reading Paul in Context and Conversation -- 5. Relational Hermeneutics and Comparison as Conversation -- 6. Announcing the Human: Rethinking the Relationship between Wisdom of Solomon 13-14 and Romans 1:18-32 -- 7. Debating Diagonal Justice: The Epistle of Enoch and Paul in Theological Conversation -- 8. Scandalous and Foolish: Defining Grace with Pseudo-Solomon and St. Paul -- Part Three: Reading Paul with Readers of Paul -- 9. The Grammar of the Gospel: Justification as a Theological Criterion in the Reformation and Galatians -- 10. The Texts of Paul and the Theology of Thomas Cranmer -- 11. The Christocentrism of Faith in Christ: Martin Luther's Reading of Galatians 2:16, 19-20 -- 12. Until Christ: Advent Again and Again in Martin Luther's Interpretation of Galatians.
Includes bibliographical references (pages 233-249) and indexes.
Keywords: Paul, -- the Apostle, Saint; Bible. -- Theology; RELIGION / Biblical Commentary / New Testament / Paul's Letters; RELIGION / Christian Theology / General